Answer:
The balanced equation is given below:
SO4^2−(aq)+ Sn^2+(aq) + 4H^+(aq) → H2SO3(aq)+ Sn^4+(aq) + H2O(l)
The coefficients of the reactants are: 1, 1, 4
The coefficients of the products are: 1, 1, 1
Step-by-step explanation:
Step 1:
The equation for the reaction. This is given below:
SO4^2−(aq)+ Sn^2+(aq) + –––→ H2SO3(aq)+ Sn^4+(aq) + –––
Step 2:
Inclusion of H+ and H2O into the equation. This is illustrated below:
SO4^2−(aq)+ Sn^2+(aq) + H^+(aq) → H2SO3(aq)+ Sn^4+(aq) + H2O(l)
Step 3:
Balancing the equation.
SO4^2−(aq)+ Sn^2+(aq) + H^+(aq) → H2SO3(aq)+ Sn^4+(aq) + H2O(l)
The above equation can be balanced as follow:
There are total 4 atoms of H on the right side and 1 atom on the left side. It can be balance by putting 4 in front of H^+ as shown below:
SO4^2−(aq)+ Sn^2+(aq) + 4H^+(aq) → H2SO3(aq)+ Sn^4+(aq) + H2O(l)
Now the equation is balanced.
The coefficients of the reactants are: 1, 1, 4
The coefficients of the products are: 1, 1, 1